2008
DOI: 10.1021/la802112h
|View full text |Cite
|
Sign up to set email alerts
|

Probing Surface Charge Potentials of Clay Basal Planes and Edges by Direct Force Measurements

Abstract: The dispersion and gelation of clay suspensions have major impact on a number of industries, such as ceramic and composite materials processing, paper making, cement production, and consumer product formulation. To fundamentally understand controlling mechanisms of clay dispersion and gelation, it is necessary to study anisotropic surface charge properties and colloidal interactions of clay particles. In this study, a colloidal probe technique was employed to study the interaction forces between a silica probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 71 publications
(163 reference statements)
7
76
1
Order By: Relevance
“…Effective surface potentials of muscovite, silica glass, magnetite and zircon as function of the pH. Muscovite mica, silica glass and zircon were measured using AFM (for details see electronic annex) and compare well with values reported in the literature (Zhao et al, 2008;Grabbe and Horn, 1993;Mao et al, 1994;Kirby and Hasselbrink, 2004) using various different techniques. The indicated range of values for magnetite is taken from zeta potential measurements (Sun et al, 1998).…”
Section: Discussionmentioning
confidence: 84%
“…Effective surface potentials of muscovite, silica glass, magnetite and zircon as function of the pH. Muscovite mica, silica glass and zircon were measured using AFM (for details see electronic annex) and compare well with values reported in the literature (Zhao et al, 2008;Grabbe and Horn, 1993;Mao et al, 1994;Kirby and Hasselbrink, 2004) using various different techniques. The indicated range of values for magnetite is taken from zeta potential measurements (Sun et al, 1998).…”
Section: Discussionmentioning
confidence: 84%
“…In addition, this change does not mean that water becomes more alkaline at lower temperatures because, in the case of pure water and according to Le Châtelier's principle, there is always the same concentration of hydrogen and hydroxide ions and, hence, the water is still neutral (pH = pOH) even if its pH changes. The pH 7.47 at 0 • C is simply the new way of referencing neutral water pH at 0 • C. In addition, assuming that the surface potential has an influence on the background signal, this will not change even if the pH changes with temperature because the surface potential values of the muscovite basal plane (the surface under study) is pH independent in the range of pH 5.6 to 10 (Zhao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there has been to date no direct way to probe the charge density on the edge and to measure the deprotonation free energies of the different sites. Another indirect strategy to determine the overall protonation state of clay edges has been proposed by Zhao et al who found using Atomic Force Microscopy that the force between a silica tip and a surface consisting of muscovite edges turned from repulsive at pH $10 to attractive at pH $6, from which they concluded that these edge surfaces had a point of zero charge of pH 7-8 (Zhao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%